A case report of sustained remission after radiotherapy combined with ICI in NEPC with primary drug resistance to chemotherapy - Li, Tengfei; Wang, Yanan; Jiang, Yueqiang; Wu, Zixi; Hu, Zhiquan; Wang, Zhihua; Yang, Chunguang (Frontiers in Oncology, 2024)
Advanced prostate cancer (PCa) is usually treated initially with androgen deprivation therapy (ADT). Although they experience a period of disease regression, most patients progress to metastatic castration-resistant prostate cancer (mCRPC). Patients with mCRPC now have an unprecedented number of approved treatment options, including chemotherapies, hormone therapies, targeted therapies, etc. However, the improvement of overall survival (OS) in patients with mCRPC and its special subtype neuroendocrine prostate cancer (NEPC) is limited. In recent years, with the use of immune checkpoint inhibitors (ICIs), such as PD1/PDL1 and CTLA4 inhibitors, immunotherapy has once again become a promising treatment choice to stimulate antitumor immunity. However, the efficacy of NEPC receiving ICI has not been reported. Here, we describe a patient with mCRPC who developed primary resistance to current endocrine and chemotherapy regimens and progressed to mCRPC with NEPC as the main component, showing a significant and lasting response to PD1 monoclonal antibody combined with radiotherapy.